The negotiation and implementation of intellectual property rights in preferential trade agreements: an analysis of the roles of the U.S. Congress and interest groups (1995 - 2012) - Teodoro, João Paulo Hernandes (2020)
The United States has a complex legal and institutional setting in place for the negotiation and implementation of international trade agreements. Such framework defines the roles of the president, Congress, and private advisory committees. This dissertation analyzes how such actors interacted to negotiate and implement the intellectual property rights included in preferential trade agreements from 1995 - 2000 and 2001 - 2012. The analysis of the first period relies on statements by members of the United States Congress and concludes that the intellectual property rights negotiated with trade partners influenced the overall U.S. trade policy and the domestic patent legislation. As regards the second period, we focus on the intellectual property rights applied to the production and trade of pharmaceuticals because since 2001 health-related concerns had become key trade-related issues. The analysis of the 2001 - 2012 period also relies on official reports produced by industry advisory committees. We identified patterns in views expressed by members of Congress and concluded that the influence of the committees was limited in scope and in time. Since both domestic and international factors influenced the U.S. trade policy at that time, throughout this dissertation we rely on theories about the two-level interactions.